The affect of grip width on bench press performance and risk of injury - Green, C. M.; Comfort, P. (Strength and Conditioning Journal, 2007)
Bodybuilders, athletes, and recreational lifters select a grip width during the bench press that they believe will produce a greater force output. Research has demonstrated that a wide grip (>1.5 biacromial width) may increase the risk of shoulder injury, including anterior shoulder instability, atraumatic osteolysis of distal clavicle, and pectoralis major rupture. Reducing grip width to .1.5 biacromial width appears to reduce this risk and does not affect muscle recruitment patterns, only resulting in a </= 5% difference in one repetition maximum.